Coronomics, Financial support for the Economy and its Zombie-ing (In the Context of the Fifth Factor of Production) - V. Papava; M. Chkuaseli (Финансы: теория и практика, 2021)
The paper examines the impact of the COVID-19 pandemic on the economy and the corresponding atypical economic crisis, the role of the economic ability of the government during this crisis, aspects of financial support for the economy and the peculiarities of the zombie economy. The aim of the study is to research the actions of the economic ability of the government as an independent factor of production in the context of the COVID-19 pandemic, contributing to the unfolding of the process of zombie-ing the economy. The research uses the methods of deduction and induction, analysis and synthesis, analogy and abstraction. The special functions of the government are considered within the context of the economic crisis caused by the COVID-19 pandemic; particularly, we refer to the recognition of the fifth factor of production of the economic ability of the government. The main features of this atypical crisis are characterized. It is shown that the process of deglobalization during the COVID-19 pandemic characterizes the deglobalization of the economic ability of the government and that this process is temporary, since overcoming the global phenomenon of the pandemic and the economic crisis caused by it requires exclusively global efforts and measures. Particular attention is focused on the financial support of the economy from the economic ability of the government within the context of this economic crisis. The conclusion is that this support contributes to the process of zombie-ing the economy which took on a global character during the global financial and economic crisis of 2007–2009 and continued after its completion. Zombie-ing the economy is the result of a conflict between the political interests of the government and its economic ability when the latter is not able to overcome the barrier created by the former. A solution to this problem is possible through changes in bankruptcy legislation when its main principle of avoiding the unwanted bankruptcy of firms will be replaced by the principle of liquidation of unviable firms. Such a change in bankruptcy legislation can be implemented only during the economic upswing.